(untitled) (Indonesian Health Justice Review, 2025)
Indonesia’s elderly population is growing rapidly, yet the healthcare system faces significant challenges in providing adequate long-term care services for older adults. This paper examines the gaps in healthcare access and policy frameworks for elderly Indonesians, focusing on long-term care and age-related health services. Using an analysis of healthcare policies, interviews with elderly individuals and caregivers, and data on healthcare utilization, the study identifies key issues in providing quality care for the aging population. These include the lack of specialized geriatric care, limited financial support for long-term care, and inadequate home care services. The paper argues that these gaps contribute to health inequities and hinder the ability of older adults to access the care they need, exacerbating social isolation and health disparities among the elderly. Recommendations include strengthening the national policy framework on aging, expanding public and private sector investment in geriatric healthcare services, and ensuring that long-term care is affordable, accessible, and of high quality. The paper concludes that addressing these gaps is essential for achieving health justice for Indonesia’s elderly population, ensuring that aging citizens can live with dignity and access the care they deserve.